Scripted Song-based Audio Media and Its Effect toward the Fifth Grade Students' English Competence in Kubutambahan Sub-district 1 in Academic Year 2014-2015 - ., I Wayan Eri Kurnia; ., Dra.Ni Made Ratminingsih, MA; ., Dr. I Gede Budasi,M.Ed,Dip.App.Lin (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini adalah sebuah studi experimen yang menyelidiki efek dari penggunaan scripted song-based audio media pada kompetensi bahasa Inggris yang dimiliki oleh siswa kelas 5 di gugus 1 Kecamatan Kubutambaha, Buleleng-Bali pada tahun ajaran 2014/2015. Desain penelitian ini adalah post-test only control group design dan menggunakan teknik random sampling untuk menentukan sample penelitian. SDN 1 Kubutambahan ditentukan sebagai grup experimen yang kemudian diberikan perlakuan berupa scripted song-based audio media dan SDN 2 Kubutambahan ditentukan sebagai grup control yang kemudian diberikan perlakuan berupa conventional teaching. Hasil dari analisis data menunjukan bahwa grup experimen mencapai kompetensi bahasa Igggris yang lebih tinggi daripada grup control.itu dibuktikan oleh rata-rata nilai mereka dimana siswa grup experimen memperoleh nilai 90.17 dan siswa grup control memperoleh nilai 79.85. Hasil dari t-test juga membuktikan bahwa scripted song-based audio media memberikan efek signifikan terhadap kompetensi bahasa Inggris yang dimiliki oleh siswa-siswa kelas 5 di Subdisktrik 1, Kubutambahan.Kata Kunci : media audio, kompetensi bahasa Inggris, scripted song, This study was an experimental study which investigated the effect of scripted song-based audio media on the fifth grade students’ English competence in Kubutambahan Sub-district 1, Buleleng-Bali in academic year 2014/2015. The design of this study was post-test only control group design and used a random sampling technique to determine the sample. SDN 1 Kubutambahan was determined as the experimental group and further treated by scripted song-based audio media and SDN 2 Kubutambahan was determined as the control group and further treated by conventional teaching technique. The results of data analysis show that the experimental group students achieved a higher English competence than the control group. It was proven by their mean score where the experimental group students got 90.17 and the control group got 79.85. The result of the t-test also proves that scripted song-based audio media gave significant effect on the fifth grade students’ English competence. In conclusion, scripted song-based audio media gave significant effect on the fifth grade students’ English competence in Kubutambahan Sub-district 1.keyword : audio media, English competence, scripted song,